Kinerja Sistem Agribisnis Cabai Merah Pada Kelompok Tani Tunas Harapan - Rania Alisa Syifawanda Yasmin; Dyah Aring Hepiana Lestari; Lina Marlina (Hasanuddin University, 2022)
This research aims to analyze the performance of red chili agribusiness system at Tunas Harapan Farmer Group in Binjai Ngagung Village, Bekri Sub District, Central Lampung. The performance of red chili agribusiness system that is assessed consists of procurement of the production facilities subsystem, the farming subsystem, the processing subsystem, the marketing subsystem, and the supporting services system. This research was conducted from December 2021 to January 2022. The basic method used in this research is a case study method involving 42 red chili farmers who are members of farmer groups, 4 traders who were selected by the census method, 2 wholesalers, and 2 retailers who were selected by the snowball sampling method. The data analysis method was carried out using the agribusiness system index. The results showed that the red chili agribusiness system in the Tunas Harapan Farmer Group still was not good with a total score of 13,83 from a maximum value of 18,90 or 73,17%. The subsystem index for the procurement of production, farming, processing facilities, and supporting services are in the good category. Meanwhile, the index of the marketing subsystem is not good.